Global trends and disparities in ischemic heart disease attributable to high systolic blood pressure, 1990–2021: Insights from the global burden of disease study - Zhenhua Zhuang; Qiuju Wang; Haifeng Li; Shenghong Lan; Yanru Su; Yue Lin; Peng Guo (PLoS ONE, 2025)
Objective To comprehensively assess the global, regional, and national burden of ischemic heart disease (IHD) attributable to high systolic blood pressure (HSBP). Methods Using the Global Burden of Disease (GBD) 2021 dataset, we conducted a systematic analysis of mortality, disability-adjusted life years (DALYs), and their age-standardized rates (ASRs) for HSBP-related IHD from 1990 to 2021. We stratified data by sex, age (25–95 + years), and sociodemographic index (SDI) categories (Low, Low-Middle, Middle, High-Middle, and High), and examined geographic disparities across 21 regions and 204 countries. Temporal trends were assessed using estimated annual percentage change (EAPC), and smoothed curve modeling and Spearman’s correlation were applied to evaluate associations between SDI and ASRs. Results Globally, the absolute number of DALYs attributable to HSBP-related IHD rose substantially from 1990 to 2021, although ASRs decreased over the same period. Males consistently shouldered a larger proportion of the burden, yet women experienced a relatively faster decline in DALY and mortality ASRs. Notable regional disparities were observed, with Central Asia, Eastern Europe, and North Africa & Middle East demonstrating higher burdens despite downward trends, whereas certain low-to-middle SDI regions and select Asian and African countries exhibited rising ASRs. Variations in SDI also correlated with shifting patterns in HSBP-related IHD burden, highlighting the importance of socioeconomic factors. Conclusion This study underscores the significant global burden of IHD attributable to HSBP, with substantial heterogeneity by sex, age, and geographic setting. The findings emphasize the need for context-specific public health interventions, such as intensified hypertension screening, early detection, and management strategies.